New Zealand : Financial Sector Assessment Program-Detailed Assessments of Observance of Standards and Codes-International Organization of Securities Commission (IOSCO)-Objectives and Principles of Securities Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper evaluates the Observance of Standards and Codes on the International Organization of Securities Commission (IOSCO) Objectives and Principles of Securities Regulation for New Zealand. New Zealand equity markets are comparatively small with market capitalization of about 44 percent of GDP. Reflecting a preference for property investment, ownership of New Zealand-listed equities remains mostly in the hands of offshore investors and domestic institutional investors, with only about one-fourth held directly by households. Securities market intermediaries include sharebrokers, futures dealers, investment advisers, and managers of collective investment schemes, including contributory mortgage brokers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet